Abortion terminology: views of women seeking abortion in Britain. Issue 4 (11th July 2017) - Cameron, Sharon; Lohr, Patricia A; Ingham, Roger
Abstract : Background: Controversy exists as to whether 'abortion or 'termination of pregnancy' should be used by health professionals during interactions with women and in published works. Methods: Self-administered anonymous questionnaires were distributed to women attending 54 abortion clinics in Scotland, England and Wales during a 4-month period in 2015. Responses were coded and analysed using SPSS. Descriptive statistics were generated and responses compared by demographic characteristics. The main outcome measures were the proportion of respondents reporting that they found the terms 'abortion' and 'termination of pregnancy' to be distressing, and women's preferred terminology for referring to induced abortion. Results: Surveys were completed by 2259 women. The mean age of the respondents was 27(range 13–51) years; 82% identified as white, 51% had children and 36% had previously undergone abortion. Thirty-five percent indicated that they found the word 'abortion' distressing compared with 18% who reported that 'termination of pregnancy' was distressing ( p < 0.001). Forty-five percent of respondents expressed a preference for 'termination of pregnancy' and 12% for 'abortion'. Sixteen percent would choose either term. This pattern of results did not vary statistically by age, reproductive history, country of residence, ethnicity or level of deprivation. Conclusions: Most women seeking abortion did not find the terms 'abortion' or termination of pregnancy' distressing. When given a choice of terms, more women who expressed a preference chose 'termination of pregnancy'. Healthcare professionals should be sensitive to preferences for terminology when communicating with women seeking abortion.